STRATEGIES AND CONSTRAINTS OF EFL STUDENT CITATION IN ACADEMIC WRITING COURSES - Suci Amelia; Fahrus Zaman Fadhly (Indonesian Journal of Learning and Instruction, 2025)
This study explores the complex interplay between generative AI tools and citation practices among EFL (English as a Foreign Language) students in academic writing contexts. Using a qualitative descriptive approach, the research investigates students’ conceptual understanding, technical challenges, emotional struggles, and institutional constraints in managing citation tasks. Data from 15 participants reveal a range of issues—from confusion about when and how to cite, overreliance on AI-generated references, to anxiety over paraphrasing and plagiarism. While tools like ChatGPT, Grammarly, and Mendeley offer assistance, the absence of proper guidance often leads to misuse and ethical ambiguity. The findings underscore the urgent need for integrated citation instruction, AI literacy, and ethical training in higher education. The study concludes with student-driven recommendations for improving citation education through hands-on workshops, consistent policies, and increased access to credible academic resources.